2017
DOI: 10.1038/s41559-016-0069
|View full text |Cite
|
Sign up to set email alerts
|

The evolution and population diversity of human-specific segmental duplications

Abstract: SUMMARYSegmental duplications contribute to human evolution, adaptation and genomic instability but are often poorly characterized. We investigate the evolution, genetic variation and coding potential of human-specific segmental duplications (HSDs). We identify 218 HSDs based on analysis of 322 deeply sequenced archaic and contemporary hominid genomes. We sequence 550 human and nonhuman primate genomic clones to reconstruct the evolution of the largest, most complex regions with protein-coding potential (n=80 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
192
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 154 publications
(207 citation statements)
references
References 79 publications
(98 reference statements)
9
192
1
Order By: Relevance
“…Over the course of human evolution, human brain volume has nearly tripled compared to chimpanzees (53), likely due to differential expression of genes during brain development (6, 8, 54). We investigated the association of structural variation with changes in human–chimpanzee brain gene expression using cerebral organoids as a proxy for brain expression differences (55).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the course of human evolution, human brain volume has nearly tripled compared to chimpanzees (53), likely due to differential expression of genes during brain development (6, 8, 54). We investigated the association of structural variation with changes in human–chimpanzee brain gene expression using cerebral organoids as a proxy for brain expression differences (55).…”
Section: Resultsmentioning
confidence: 99%
“…Although we observe the same trend in excitatory neurons, the effect did not reach significance. As a control, we repeated the same analysis for genes mapping to human-specific SDs (54), a form of structural variation not accessed in this study. Genes mapping to human SDs were upregulated in radial glial and excitatory neurons when compared to chimpanzee (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Gene families, which correspond to sets of genes generated by duplications from a common ancestor, can originate from a WGD or an SSD event, or from a mixture of both. Furthermore, the identification of duplicated genes that emerged following the human-chimpanzee divergence has attracted important attention because of their potential contribution to human-specific traits, and in particular to brain complexity (Sudmant et al 2010;Dennis and Eichler 2016;Dennis et al 2017). Notably, the study of the interplay between several genes of the SRGAP2 (Slit-Robo Rho GTPase-activating protein 2) and ARHGAP11 (Rho-type GTPase-activating protein 11) families has revealed a functional association of the human-specific duplicated genes SRGAP2C and ARHGAP11B with an increase in both dendritic spine density and cortical neuron population (Charrier et al 2012;Florio et al 2015).…”
Section: Cnsmentioning
confidence: 99%
“…To refine again the association between duplication age and tissue-specificity, we performed enrichment analyses using a short list of paralogs that came from human-specific duplication events (see Materials and Methods) (Dennis et al 2017) and found no significant associations (see Supplementary Materials, table S19). To obtain a complementary view of this tissue-specificity loss for very recent duplications, we examined the distribution of the Tau scores of paralogs according to their phyletic age (see Supplementary Materials, fig.…”
Section: / Evolutionary and Genomic Properties Of Tissue-specific Pamentioning
confidence: 99%
See 1 more Smart Citation